EFKTIFITAS MEDIA SEMPOA UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN BULAT 1-10 UNTUK ANAK TUNAGRAHITA RINGAN KELAS II C SLB FANREDHA PADANG - Ronalis - (Universitas Negeri Padang, 2015)
Abstract: This research was derived from the problem found in the field indicating that a student with light mental retardation in class II C of SLB Fanredha Padang got difficulties in the sums of integers from 1 to 10. He was not able to recognize and write the numbers and could not sum them. This research was intended to see the effectiveness of Sempoa in improving the student’ ability in the sums of integers `from 1 to 10. This was a Single Subject Research which used A-B-A design. The data gotten was analyzed by using visual analysis of graphic. The subject of the research was a student with light mental retardation in class II C. The variable was measured by using percentage technique in which the number of the items answered correctly was presented in percentage. The result of the research showed that the use of Sempoa was effective to improve the student with light mental retardation ability in the sums of integers from 1 to 10. The observation was done in three sessions. The baseline session (A) consisted of six observations which were done in different days. In this session, the student’s ability in the sums of integers from 1 to 10 was 20%, 0%, 40%, 20%, 20%. In the intervention session (B) through which the Sempoa was applied, eight observations were done. In this session, it was figured out that the student’s ability was 70%, 70%, 80%, 60%, 80%, 70%, 80% and 80%. The baseline session (A1) consisted of five observation. In this session, the student’s ability improved which was 60%, 80%, 90%, 90% and 90%. Based on the research findings, it was concluded that the use of Sempoa was effective to improve the student with light mental retardation ability in the sums of integers from 1 to 10 at SLB Fanredha Padang. Related to this finding, it was suggested to the teachers to use Sempoa to improve the students with light mental retardation understanding in the sums of integers. Kata Kunci : Tunagrahita Ringan ; kemampuan ; penjumlahan bilangan ; sempoa